Failure analysis with a focus on thermal aspect towards developing safer Na-ion batteries - Li, Yuqi; Lu, Yaxiang; Chen, Liquan; Hu, Yong-Sheng (Chinese physics B, 2020)
Safety requirements stimulate Na-based batteries to evolve from high-temperature Na–S batteries to room-temperature Na-ion batteries (NIBs). Even so, NIBs may still cause thermal runaway due to the external unexpected accidents and internal high activity of electrodes or electrolytes, which has not been comprehensively summarized yet. In this review, we summarize the significant advances about the failure mechanisms and related strategies to build safer NIBs from the selection of electrodes, electrolytes and the construction of electrode/electrolyte interfaces. Considering the safety risk, the thermal behaviors are emphasized which will deepen the understanding of thermal stability of different NIBs and accelerate the exploitation of safe NIBs.